Median Mononeuropathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The clinical and electromyographic characteristics of median mononeuropathy in 17 children, 6 girls and 11 boys, aged 5-17 years, are reported from the Departments of Neurology, Children's Hospital, Boston and the Lahey Clinic, Burlington, MA.